2008
DOI: 10.1007/s12032-008-9094-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of p53 and CD31 in astrogliomas

Abstract: The estimation of p53 and CD31 could be used as good tools to assess the grade, prognosis, and aggressiveness of the astroglial tumors. Thus, the two markers can be used as adjunct to the diagnosis and stratification of the high grade from the low-grade intrinsic brain astrogliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In addition to its role in determining tumor cell survival and growth, MAPK signaling can influence tumorigenesis (30), and through this, some cannabinoids have also been shown to be antiangiogenic and antiinvasive (31). Our data support this, as the lessening of the red, bloody hue of the tumor mass in the brain sections also correlated with a reduction in the endothelial maker of angiogenesis/neovascularization CD31 (32). It is intriguing to speculate at this time, that in addition to hindering tumor growth through an antiproliferative effect, the treatment was also reducing cancer development by inhibiting tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to its role in determining tumor cell survival and growth, MAPK signaling can influence tumorigenesis (30), and through this, some cannabinoids have also been shown to be antiangiogenic and antiinvasive (31). Our data support this, as the lessening of the red, bloody hue of the tumor mass in the brain sections also correlated with a reduction in the endothelial maker of angiogenesis/neovascularization CD31 (32). It is intriguing to speculate at this time, that in addition to hindering tumor growth through an antiproliferative effect, the treatment was also reducing cancer development by inhibiting tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…The pan-endothelial marker CD34 was expressed in the significant portion of giant cell GBM (73%) as well as non-giant cell GBM (56%) with the strong widespread staining in 55% and 25% of tumors, respectively [ 60 ]. The significant relationship between the expression of pan-endothelial marker CD31 and tumor grade was found in the study with 45 astrocytomas where the highest expression was observed in GBM samples (P = 0.001) [ 61 ]. Another study examined the degree of angiogenesis in GBM measured by microvessel density (MVD) using both pan-endothelial marker CD31 and marker CD105/endoglin, which preferentially react with active endothelial cells in angiogenic tissue [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sub-population may also have an enhanced proliferative capacity and it has been proposed that this T cell population may enhance susceptibility to autoimmune disease (48). Furthermore, some CD31-expressing tumour cells are less apoptotic and associated with a poorer prognosis for the patient (49, 50).…”
Section: Discussionmentioning
confidence: 99%